6(1-3x)=15x-14+2(1-3x)

Simple and best practice solution for 6(1-3x)=15x-14+2(1-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(1-3x)=15x-14+2(1-3x) equation:



6(1-3x)=15x-14+2(1-3x)
We move all terms to the left:
6(1-3x)-(15x-14+2(1-3x))=0
We add all the numbers together, and all the variables
6(-3x+1)-(15x-14+2(-3x+1))=0
We multiply parentheses
-18x-(15x-14+2(-3x+1))+6=0
We calculate terms in parentheses: -(15x-14+2(-3x+1)), so:
15x-14+2(-3x+1)
determiningTheFunctionDomain 15x+2(-3x+1)-14
We multiply parentheses
15x-6x+2-14
We add all the numbers together, and all the variables
9x-12
Back to the equation:
-(9x-12)
We get rid of parentheses
-18x-9x+12+6=0
We add all the numbers together, and all the variables
-27x+18=0
We move all terms containing x to the left, all other terms to the right
-27x=-18
x=-18/-27
x=2/3

See similar equations:

| 65=9u-7 | | 5/12x+1/6=11/12 | | 2-3x:4=1 | | p-2/3=2/5 | | x-11+x-39+38=180 | | 5/6x+1/4=2/3 | | 16=1-5u | | 3n/20=5/12 | | -7=y/6 | | 2x−5=2(x−5) | | x+3/8=-4 | | x+6=2x–8 | | x+43+2x+86=180 | | 10(x-1)=2x-7 | | 3t=2/7t= | | 5w-9=-24 | | r+13/10=4 | | 2x-x^2+8=0 | | u/20+6=6 | | 12-1/3x=-27 | | 6x-47=x+4 | | 2(1-2x)=2(2x-1) | | 4x-2(1-2x)=3 | | 20x+25=19x20 | | 7x=223 | | (X-5)(x+2)=55 | | x^2-25x-12x+150=0 | | 4-4*7+x=-27 | | 6x-47+x+4=180 | | 102=8x-6 | | 5+|m|=7.3 | | t/8+29=25 |

Equations solver categories